Coordination Compounds Featuring Non-Toxic Chiral 1,4-Dicarboxylic Acids and Copper(II) - Marius Kremer; Jan van Leusen; Ulli Englert (Crystals, 2020)
Six new coordination compounds of copper cations and 1,4-dicarboxylic acids have been synthesized and structurally investigated. Aspartic acid (H2asp), enantiopure, racemic and meso tartaric acid (H2tart), di-para-toluyltartaric acid (H2dptta) and dibenzoyltartaric acid (H2dbta) represent environmentally benign water-soluble proligands which may be deprotonated for oxygen coordination. Chelating ligands such as tetramethylethylenediamine (TMEDA) and 2-aminomethylpyridine (AMPY) efficiently reduce the dimensionality of the target compounds, and additional aqua ligands complete the coordination environments. In this line of argument, the discrete mononuclear complexes [Cu(AMPY)(asp)(H2O)] and [Cu(Hdbta)2(H2O)4] were obtained; for the latter, only a preliminary structure model can be presented which, however, agrees with the powder diffraction pattern of the bulk. From enantiopure and racemic tartaric acid and TMEDA the closely related chain polymers [CuII(H2tart)(TMEDA)(H2O)2)]n were obtained; the racemic compound consists of individual homochiral strands of opposite chirality. The high steric demand of di-para-toluyltartaric acid leads to one-dimensional [Cu(dptta)(EtOH)(H2O)2]n with coordinated ethanol (EtOH) in the distant Jahn–Teller site of the coordination sphere. Cu(II), meso-tartaric acid and TMEDA aggregate to a trinuclear coordination compound [CuII2CuI(H2tart)(Htart)(TMEDA)2]. Its peripheral cations show the expected Jahn–Teller geometry of Cu(II), but the unambiguous assignment of the oxidation state +I for central cation required susceptibility measurements: their results prove the presence of only two and only very weakly interacting divalent cations, separated by a diamagnetic center.